(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Jakaria J, Dharmawanthi AB, Dairoh, Ulum MF, Anwar S, Noor RR. 2025. Short communication: Complete mitochondrial genome sequence of Bali cattle (Bos javanicus). Biodiversitas 26: 1545-1552. Bali cattle (Bos javanicus), one of the most popular indigenous cattle breeds in Indonesia, was domesticated from the wild Banteng. This study aimed to determine the complete mtDNA sequence and assess its genetic variation utilizing the Illumina NovaSeq6000 platform, marking the first time reporting the complete mitochondrial genome sequence of Bali cattle. Blood samples were collected from BBIB Singosari, Malang, East Java. DNA was extracted using the DNA Extraction Kit protocol (Promega). The total mitochondrial genome was annotated using the MITOS2 software. The result of this study showed that mitochondrial DNA (mtDNA) has a total length of 16,712 bp and comprises 37 genes with a typical structure. These include 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs, and a D-loop region. The nucleotide composition of the genome is 33.6% Adenine (A), 27.1% Thymine (T)/uracil (U), 25.8% Cytosine (C), and 13.4% Guanine (G). Phylogenetic analysis based on the complete mitochondrial genome sequences distinguished into three clades of cattle breed. Including B. javanicus (GenBank data), B. taurus, B. indicus and Bali cattle groups showed notable genetic variations. The results of this work offer genomic information capable of supporting the next investigations on the genetic structure and evolutionary background of Bali cattle.